Do voters dislike liberalizing reforms? New evidence using data on satisfaction with democracy. Issue 4 (19th February 2019) - Berggren, Niclas; Bjørnskov, Christian
Abstract: Since the early 1980s a wave of liberalizing reforms has swept over the world. Using panel data from 30 European countries in the period 1993–2015, we test the hypothesis that such reforms have led to voter dissatisfaction with democracy, since, it is argued, they have been undertaken in a non-transparent way, often during crises, and they have entailed detrimental consequences. The reform measures are constructed as distinct changes in four policy/institutional areas: government size, the rule of law, market openness, and regulation. Our results indicate that while reforms of government size are not robustly related to satisfaction with democracy, reforms of the other three kinds are – and in a way that runs counter to anti-liberalization claims. Reforms that reduce economic freedom are generally related to satisfaction with democracy in a negative way, while reforms that increase economic freedom are associated positively with satisfaction with democracy.